Weld defect detection using ultrasonic testing (UT) and phased array ultrasonic testing (PAUT) - Rabiatul Alisha Mohd Rezalman (2024)
Ultrasonic testing (UT) is a non-destructive testing (NDT) method employed for detecting defects, while phased array ultrasonic testing (PAUT) represents an advanced form of UT with additional features. This study focuses on inspecting a weldment sample using UT and PAUT techniques by employing various probe angles. The variation in probe angles leads to alterations in wave formation and defect size during the inspection process. The aim objectives of this study include examining weld defects through the utilization of different probe angles in both UT and PAUT. Three probe angles, namely 45º, 60º, and 70º, were utilized for inspection. The impact of probe angle on defect detection was assessed by analysing wave formations presented in A-scan representation and, in the case of PAUT, it can also be displayed in S-scan representation. Findings indicate that the choice of probe angle significantly influences the accuracy of defect detection. The effectiveness of each probe angle is contingent on the defect's location within the weldment. Typically, a 45º probe angle is more suitable for defects near the surface, whereas a 70º probe angle is more effective for detecting deeper-seated defects. In summary, all probe angles can be employed effectively for defect detection, but careful consideration is essential to choose the optimal method based on the defect's location.